Efeito da exposição à alteração de ph, palmitato de Sódio e glutamina em cultura de células intestinais na dosagem de peptídeos intestinais - TAKEUTI, Tharsus Dias (2017)
INTRODUCTION: The study of L cells has been highly valued for their potential of production of intestinal incretins and peptides. GLP-1 is the main incretin produced. OBJECTIVE: To evaluate GLP-1 secretion in intestinal cells of the HCT-8 strain when exposed to pH alteration conditions, glutamine supplementation and sodium palmitate. METHODOLOGY: Cells were exposed to pH 7.2 and stimulated with glutamine, sodium palmitate and pH change for 4,8 and, the culture médium was collected at 15 (T0), 30 (T1) and 60 (T2) minutes for GLP-1 and DHL dosage. RESULTS: A higher concentration of the hormone was observed in T2 compared to baseline (p = 0,02) when compared to the pH conditions, the same behavior could be observed with the sodium palmitate stimulus (p = 0,04). With the glutamine stimulus, no significant differences were observed. CONCLUSION: Based on the results, it can be suggested that pH change as well as stimulation with palmitate influences the secretion of GLP-1 in HCT-8 cells, observing a higher concentration when compared to baseline. Glutamine stimulation, at the concentration used in the study, did not prove to be a potentiator of hormone secretion. Further studies must be carried out to prove the theories.